Enhanced solar cell efficiency via reflectance on silicon wafers: laser texturing vs. anisotropic etching - Nurul Huda Abdul Razak,; Badariah Bais,; Amin, Nowshad; Kamaruzzaman Sopian,; Md. Akhtaruzzaman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Due to its high refraction index, silicon (Si) reflects a significant amount of solar light of more than 37% of the sun’s spectral range, particularly when it does not strike the surface perpendicularly. This effect consequentially reduces solar cell efficiency due to electrical and optical losses. Surface texturing is essential for increasing the cells’ photon-trapping and absorbing capabilities to improve the efficiency of low-performance solar cells. In this study, pulsed Nd:YAG lasers are used to texturize surfaces of silicon wafers. This procedure is quicker and easier and does not produce waste or pollutants. However, there are some disadvantages to laser texturing; one is that it may lower solar cell efficiency if the damaged layer caused by the laser texturing is not removed. In this study, the laser damage layer is washed off with potassium hydroxide (20%), also known as KOH. This paper also compares the reflectance of laser texturing and wet chemical etching on surfaces of crystalline silicon wafers. The PerkinElmer Lambda 950 UV-VIS-NIR Spectrophotometer results indicate that laser texturing obtains a reflectance of 1% before and 9% after KOH treatment, in contrast to wet chemical etching, which has a reflectance of 16%. Laser texturing showed some efficiency, especially when texturing silicon wafer surfaces in parallel patterns, with a conversion efficiency of about 5% and grid patterns at 7.5%. This successful outcome demonstrates that laser texturing gives silicon solar cells a good alternative to traditional texturing techniques.